Childhood trauma and lifetime syncope burden among older adults - Kenny, Rose; Mc Crory, Cathal (My University, 2017)
Objective: Vasovagal syncope is governed by the autonomic nervous system and often precipitated by highly salient emotional situations. We hypothesized that a lifetime tendency towards vasovagal syncope may be precipitated by exposure to childhood trauma. Methods: We examined data from the first wave of The Irish Longitudinal Study on Ageing (TILDA) of adults aged 50+ (n=6497) who were asked to report lifetime syncope frequency and any history of childhood sexual or physical abuse. Mediation analysis was used to assess the relative importance of pathways via which childhood trauma could plausibly increase risk of later life recurrent syncope including via depression, mid-life cardiovascular disease and frequent syncope in youth. Results: 18.2% reported a lifetime syncopal event: 4.0% frequent syncope in youth and 1.5% recurrent syncope in the last year. 10.9% reported childhood sexual or physical abuse, rising to 14.2% among those reporting any lifetime syncopal event, 21.0% with frequent syncope in youth and 20.2% with recurrent syncope in later life. In fully adjusted logistic regression models the report of childhood sexual or physical abuse was independently associated with frequent syncope in youth (OR 1.85 (CI 95% 1.27-2.71); p=0.001; OR 2.14 (1.48-3.10); p<0.001 respectively). A history of frequent syncope in youth and depression partially mediated the relationship between childhood sexual and physical abuse and recurrent syncope in later life, while mid-life cardiovascular disease was less important. Conclusion: Childhood trauma may contribute to a lifelong vasovagal tendency. Early attention should be given to the potential precipitating and perpetuating psychosocial factors affecting recurrent syncope.
PUBLISHED
Keywords: Lifetime risk, Psychiatric comorbidity, Psychology and behavior, Syncope, Syncope (fainting); Ageing